Eksplorasi Interaksi Simbolik Pengemis Online di Ekosistem TikTok - Elfryda Amelia Dhamayanti; Puti Alifa Layynasha Alamsyah; Sarah Derma Ekaputri; Salsabilla Widyarto (School of Communication Science and Media Business, 2024)
Live-streaming activities on TikTok have developed into the most popular form of content creation today because it is equipped with virtual prizes so that various types of live streaming content have emerged, one of which leads to